Devolution, democracy, and the challenge of diversity: community energy governance in Scotland - van Veelen, Bregje (The University of Edinburgh, 2017)
This research investigates the emergence of new participatory spaces in the transition towards a low-carbon society. Specifically, it focuses on the emerging spaces and roles for community groups in renewable energy governance. The role of community groups in facilitating a low-carbon transition has received much attention in recent years, but has been insufficiently studied within the wider context of evolving state-civil society relations. This research puts forward an understanding of community energy initiatives that is neither inherently celebratory nor dismissive of community action, but argues that such initiatives should be understood based on the interactions – between practices, organisations and relations – within and external to these communities. In doing so, this research adopts an interdisciplinary approach, building on insights from both geography and political science to understand how opportunities for community participation are articulated in particular geographical and political contexts. Grounding this research in Scotland shows the unique ways in which devolution – from the UK Government to the Scottish Government, but primarily through the emerging powers for community groups in Scotland – has created a set of spatially and temporally-specific spaces and practices of intervention. The devolution of energy governance, and the diversity of practices emerging through this process, also raises questions, however, about the democratic qualities of these new spaces and practices. This research specifically explores this issue through building on the emerging concept of energy democracy. ‘Energy democracy’ is a concept that has been adopted by a growing number of international civil society actors who regard the transition to law-carbon energy sources as an opportunity not only for technological innovation but also for wider socio-economic transformation. Invoking an image of associative democracy, those advocating for greater energy democracy consider self-governing community groups as best placed to ensure that the transition towards a low-carbon society is one that is more inclusive, democratic and just. While energy democracy, like related concepts of energy citizenship and energy justice, aims to combine technological and social transformation, its activist roots also means it is noticeably different. This is evident in two ways. First, the current body of literature is largely uncritical and rather vague in nature. The second consequence of the activist roots of energy democracy is that it is diverse in its framing of the issue and its formulation of desired transition pathways. As its main contribution to existing academic debate, my thesis explores and expands the conceptual foundations of ‘energy democracy’ by evaluating its connections to different political theories, and the consequences of different interpretations for energy democracy research and practice. Secondly, I seek to develop the empirical evidence base for energy democracy. The current, primarily activist, literature on energy democracy often assumes rather than demonstrates that the forms of governance it promotes are more democratic than the status quo. This PhD therefore sets out to analyse the complex and varied ways in which local communities practice energy governance in Scotland. First, I introduce a quantitatively-developed typology of community energy projects in Scotland to highlight the diverse nature of the sector. Subsequently I demonstrate through qualitative interviews with community groups how the diversity of the sector (both within and between groups) both contributes to, and challenges, the democratic claims made for and by community energy. In the final part I show that the hybridity of spaces created by, and for, community energy intermediaries reflect the interactions between policy and community-action. Through a focus on the interaction between actors at different governance levels, my research helps to improve an understanding of the creation and contestation of new spaces of intervention in the Scottish energy transition as a process that not only reflects a broader (re)structuring of state-civil society relations, but also provides an early and somewhat experimental expression of such restructuring.
Keywords: renewable energy projects; community groups; energy democracy; community energy; Scottish Government policies